Design, manufacturing and applications of wearable triboelectric nanogenerators. (March 2021) - Wang, Haobin; Han, Mengdi; Song, Yu; Zhang, Haixia
Abstract: Amid the rapid flourishment of wearable electronics, the issue of power consumption has become increasingly prominent. With an extremely simple and universal configuration, triboelectric nanogenerators (TENGs) have emerged and performed huge advantages in converting low-frequency mechanical energy into electricity. Thus, TENGs in wearable forms are expected to capture the energy in human motions and in-situ drive wearable devices. Moreover, such a type of energy conversion allows us to excavate the rich information behind the output signals. In this review, we first introduce the basic design of TENGs suitable for wearable devices, including material selection, process modulation and optimization of the form factor. Then, we elaborate on three key roles that wearable TENGs play in the current era of smart Internet of Things (IOT), i.e., active sensors, actuators, and human-machine interfaces. Next, we summarize the progress of wearable TENG-powered systems at the performance level and process level. In the end, we make concrete prospects for this technology to move further into the actual market and approach the general public lives. Graphical Abstract: Triboelectric nanogenerators (TENGs) have built a bridge between human's daily routine and wearable electronics due to their ability to capture the energy in human motions. Moreover, such a type of energy conversion allows us to excavate the rich information behind the output signals. In this review, we will show the latest progress of TENGs in the wearable field from the basic design to practical applications in detail. Wearable forms and working modes of TENGs. ga1 Highlights: The basic design of wearable TENGs including materials selection, process modulation and performance optimization. Three roles played by wearable TENGs at device level, i.e., active sensors, actuators, and human-machine interface. The progress of wearable TENG-powered systems at the performance level and process level. The concrete prospects for this technology to move further into actual market and daily life.